Sleep Deprivation and Subchronic Arsenite Exposure Synergistically Induced Skeletal Muscle Aging by Disrupting Melatonin and Cortisol Secretion in Mice - Hongyi Yang; Xingyu Chen; Xuanfeng Yu; Baofei Sun; Junyan Tao; Xiong Chen (Toxics)
In recent years, the influence of environmental factors on organismal aging has garnered increasing attention. Studies have shown that sleep deprivation and environmental pollutants could accelerate the emergence of multiple organismal aging phenotypes. In addition, studies have shown that chronic exposure to sodium arsenite (iAs) induces skeletal muscle atrophy and the inhibition of melatonin secretion in rats. This study aimed to reveal the synergistic effect of sleep deprivation and arsenite exposure on skeletal muscle aging, including reduced limb grip strength and skeletal muscle mass, along with the serum levels of melatonin (MT) and cortisol (COR) in C57BL/6J mice. The results demonstrated that while exposure to arsenite for 12 weeks or sleep deprivation (SD) for 4 weeks did not exert significant effects on limb grip strength or skeletal muscle mass, their combination exhibited a synergistic effect on skeletal muscle aging. Notably, the iAs+SD group exhibited a significant decline in limb grip strength by Week 12, accompanied by a reduced gastrocnemius muscle mass and muscle index. The pathological analysis showed muscle fiber atrophy, a shift towards slow-twitch muscle fibers (type I), and shortened telomere length. Additionally, oxidative damage was increased in the SD and iAs+SD groups, with decreased levels of SOD and GPx and elevated levels of MDA in the iAs+SD group. The serum MT level and MT/COR ratio were significantly reduced, while the serum COR level was elevated in the iAs+SD group compared to the other groups. A correlation analysis further revealed that the serum MT level and the MT/COR ratio were positively correlated with limb grip strength, muscle index, and telomere length, whereas the serum COR level exhibited negative correlations with these parameters. These findings suggest that sleep deprivation and subchronic exposure to arsenite synergistically induce skeletal muscle aging, and that the disruption of the balance between MT and COR potentially serves as a significant risk factor.